Transient free convective radiative flow between vertical parallel plates heated/cooled asymmetrically with heat generation and slip condition - Gaur, P.K.; Sharma, Ram Prakash; Jha, Abhay Kumar (Zielona Góra: Uniwersytet Zielonogórski)
Investigation of an MHD convective flow of viscous, incompressible and electrically conducting fluid through a porous medium bounded by two infinite vertical parallel porous plates is carried out. Forchheimer-Brinkman extended Darcy model is assumed to simulate momentum transfer within the porous medium. A magnetic field of uniform strength is applied normal to the plates. The analytical results are evaluated numerically and the presented graphically to discuss in detail the effects of different parameter entering into the problem.
Keywords: MHD; slip flow; heat generation; thermal radiation